A parenting intervention for middle childhood: An expansion of a Circle of Security intensive individual protocol. (17th June 2019) - Andrews, Ellen
Abstract : The intensive Circle of Security intervention is an attachment-based program that utilises video feedback to support parents to understand and respond to their children's attachment needs. The original group format was developed into an individual protocol for flexible delivery and broad dissemination. This protocol, described elsewhere, has been previously meaningfully applied to caregiver-child dyads up to preschool age. The present case study describes an expansion of the protocol's applicability to dyads in middle childhood by demonstrating its use with a mother who presented with difficulties managing the externalising behaviours of her 8-year-old daughter.